Synaptic activity and nuclear calcium signaling protect hippocampal neurons from death signal-associated nuclear translocation of FoxO3a induced by extrasynaptic N-methyl-D-aspartate receptors - Dick, Oliver; Bading, Hilmar (The journal of biological chemistry, 2010)
Synaptic activity and the generation of nuclear calcium signals promote neuronal survival through a transcription-dependent process that is not fully understood. Here we show that one mechanism of activity-induced acquired neuroprotection involves the Forkhead transcription factor, FoxO3a, which is known to induce genomic death responses upon translocation from the cytosol to the nucleus. Depletion of endogenous FoxO3a using RNA interference renders hippocampal neurons more resistant to excitotoxic cell death. Using a FoxO3a-green fluorescent protein (GFP) fusion protein to monitor in real time the localization of FoxO3a in hippocampal neurons, we found that several cell death inducing stimuli, including the stimulation of extrasynaptic N-methyl-D-aspartate receptors, growth factor withdrawal, and oxygen-glucose deprivation, caused a swift translocation of FoxO3a-GFP from the cytosol to the cell nucleus. This translocation was inhibited in hippocampal neurons that had undergone prolonged periods of synaptic activity before exposure to cell death-inducing conditions. The activity-dependent protection from death signal-induced FoxO3a-GFP nuclear translocation required synaptic N-methyl-D-aspartate receptor activation and was dependent on nuclear calcium signaling and calcium/calmodulin-dependent protein kinase IV. The modulation of nucleo-cytoplasmic shuttling of FoxO3a may represent one mechanism through which nuclear calcium-induced genomic responses affect cell death processes.